Assessing sustainable competitive advantage in relation with intellectual capital, knowledge management and innovativeness in women-owned SMEs in Malaysia / Che Asniza Osman, Rohana Ngah - Osman, Che Asniza; Ngah, Rohana (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
Small Medium Enterprises (SMEs) play an important role in contributing the economic growth of most nations. As the global economy slows down, entrepreneurship role becomes increasingly important to drive the pecuniary and societal well-being. In 2012, Global Entrepreneurship Monitor (GEM), reported an estimation of 126 million women have started or running new businesses in around 67 countries around the world. In addition, about 98 million women are operating established businesses. Study showed that women seem to face difficulties in moving from one phase to another to withstand the entrepreneurship process thus; they are rated lower in terms of starting venture comparing to men. This paper provides a conceptual discussion on the role of intellectual capital, knowledge management, and innovativeness in sustaining competitive advantage of women owners of SMEs. The variables investigated eventually attempts to establish and test an integrated framework for intellectual capital.